Analisis Peningkatan Kreativitas Siswa Setelah Menggunakan Modul Pembelajaran Digital Berbasis Team Based Project - Winatha, I Komang; Rusman, Tedi; Suroto, Suroto; Rahmawati , Fanni; Fitriani, Nur; Afryanto, Verdyan Nur; Salshabella, Dhea Clara (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This community service program was carried out to enhance students’ creativity through the implementation of a digital learning module based on the Team Based Project approach at MTs Al-Hidayah Rajabasa. The partner school faced challenges related to students’ low creative thinking skills and the limited use of innovative digital learning media. To address these issues, the service team provided training on the use of digital modules, facilitated project-based learning activities, and evaluated students’ creative development through pre- and post-assessments. Throughout the program, students participated in group discussions, case explorations, and project completion tasks that encouraged flexible thinking and collaborative creativity. The results showed a significant increase in students’ creativity, with the average score rising from 58 to 77.91, representing an improvement of approximately 35.31%. This positive outcome indicates that team-based project learning supported by digital modules is an effective solution for developing students’ creativity. The program is expected to serve as an alternative model for schools in integrating 21st-century skills into classroom practices.